Karakteristik Beberapa Biji Kopi Arabika Komersil di Indonesia - Yesi Desmiaty; Liliek Nurhidayati; Ni Made Dwi Sandhiutami; Reczky Muhammad Ramdhan Hasan; Kharinta Adella Meynderth; Dianita Ayu Noviastuti (Fakultas Farmasi Universitas Pancasila, 2022)
Arabica coffee is one of the mainstay commodities in the Indonesian plantation sector. Geographical differences and the environment where coffee grow can affect the characteristic, phytochemical content and antioxidant activity of the beans. The aim of this study was to determine the phytochemical characteristics and antioxidant activity of 10 items of commercial Arabica coffee beans in Indonesia. The extraction of 10 coffee beans was carried out by kinetic maceration in 1 hour with 70% ethanol, then evaporated. Each extract was examined for morphology, phytochemical screening, assay of caffeine content using HPLC method, levels of flavan-3-ol, total flavonoid content (TFC), total polyphenolic content (TPC), antioxidant determination using DPPH and FRAP methods. All bean samples showed the presence of flavonoids, alkaloids, triterpenoids, coumarins, and tannins. The chemical content determination showed caff eine content of 1.5-2.9%; flavan-3-ol content 4.85-12.38cat/g extract; TFC 9.71–23.67QE/g extract; and TPC 21.8–76.26GAE/g extract. Tests of antioxidant capacity using the DPPH reveal an inhibiting effect with varying IC₅₀ values from 19.49-81.41g/mL and using the FRAP method gave IC₅₀ values from 18.01-61.2g/mL. This study indicates that coffee samples have the same phytochemical characteristics and also have an important antioxidant activity, which justifies its potential to be developed into antioxidant nutraceuticals.